The Symbolism of Death in Taufiq Al Hakim Short Story Daqqat al-Sa’ah: A Peirce Semiotic Analysis - Adawiyah, Hilma Robiatul; Munjiah, Ma’rifatul (Mantiqu Tayr: Journal of Arabic Language, 2026)
Death in literary texts is frequently represented in an implicit manner through symbolic signs that require semiotic interpretation to access their underlying meanings. In Arabic short stories, death commonly operates as an existential motif shaped by language and narrative symbolism. This study seeks to examine the icons, indices, and symbols that construct the representation of death in Taufiq al-Hakim’s short story Daqqat al-Sa‘ah. Employing a descriptive qualitative approach with reading and note-taking techniques, the analysis is conducted using Charles Sanders Peirce’s triadic semiotic model, which consists of representamen, object, and interpretant. The findings indicate that death is articulated through recurring signs such as the sound of a ticking clock, barking dogs, specific temporal markers, power outages, medical authority, and the sudden death of Hamadah. These signs collectively generate an understanding of death as an existential condition beyond human control. This research contributes to literary semiotic studies by emphasizing death as the central semiotic structure of the narrative and reaffirming the applicability of Peirce’s semiotics in interpreting implicit meanings in Arabic literary texts. Future research may expand this approach to other Arabic works or integrate semiotic analysis with psychological and existential perspectives.